Patterns of eating behaviors, physical activity, and lifestyle modifications among Bangladeshi adolescents during the COVID-19 pandemic. - Most Zannatul Ferdous; Md Saiful Islam; Lakshmi Rani Kundu; Ummay Soumayia Islam; Rajon Banik; Shahina Pardhan (PLoS ONE)
Background Several safety measures like movement restrictions, closure of educational institutions, and social distancing measures continue over the world including Bangladesh during the COVID-19 pandemic. This study aimed to examine the patterns of eating behaviors, physical activity, and lifestyle modifications among adolescents during the COVID-19 pandemic residing in Bangladesh. Methods A cross-sectional study was performed among 490 adolescents in Bangladesh from December 2020 to May 2021. The survey was carried out through a semi-structured web-based questionnaire that asked questions about socio-demographics (i.e., age, sex, marital status, education, residence), perceived health status and quality of life, anthropometrics (i.e., height, weight), dietary habits (i.e., frequency of eating, daily intake of certain foods, number of meals eaten daily), and physical activity (i.e., modified version of the International Physical Activity Questionnaire Short Form [IPAQ-SF]), as well as, pre- and during COVID-19 information on stress, and sleep. Results During the pandemic, 43.7% participants reported weight gain; and 23.5% reported an increased number of meals per day during COVID-19. Additionally, the participants' eating habits diverged from the local balanced diet principles and were more akin to 'unhealthy' eating patterns. Though, during the COVID-19 pandemic, physical exercise slightly increased (>3 times/ week: 8.2% vs. 13.5%; p<0.001) compared to pre-COVID-19 period, the screen time for entertainment increased drastically (>5 hours/ week: 12.2% vs. 27.3%; p<0.001). Compared to the pre-pandemic, a sizeable proportion of individuals experienced more physical tiredness, emotional exhaustion, irritation, and stress (p<0.001) during the pandemic. During the pandemic, 47.5% of participants experienced different sleep difficulties. Conclusions Although lockdowns and social distancing are important safety measures to protect people from COVID-19, findings reveal that they might cause a variety of lifestyle changes, physical inactivity, and psychological issues in Bangladeshi adolescents.